Paragenetic relationship between ferromanganese and calcareous nodules in a hydromorphic toposequence - Péter Sipos; Ivett Kovács; Adrienn Tóth; Péter Németh; Attila Demény (Geoderma)
Although both ferromanganese and calcareous nodules are common in hydromorphic soils, their joint presence has rarely been evaluated. Studying their occurrence in soils forming toposequences may significantly contribute to a better understanding of their formation. We investigated the relationship between their formations in four soil profiles from a salt affected toposequence through mineralogical, micro-fabric, micro-chemical, morphological, and stable isotope analyses.Concentric ferromanganese nodules, representing the most developed nodules, were formed within the most intense groundwater fluctuation zone, whereas calcareous nodules showed a maximum in size just above the lowest groundwater level in each hydromorphic profile. Ferromanganese nodules formed slowly through matrix impregnation in the wet season under the effect of an intense groundwater fluctuation. Contrarily, calcareous nodules precipitated rapidly in cavities in the dry season following the decline of the groundwater table. Dissolution and re-precipitation were characteristic of calcareous nodules formed at shallower depths, suggesting the influence of the fluctuating groundwater on their formation, as well. The smectitic clay mineralogy of the soils affected drainage, promoting the development of a secondary groundwater fluctuation zone. Additionally, smectites provided a surface for the initial precipitation of Fe-oxyhydroxides, and facilitated the formation of cavities in the soil.In the ferromanganese nodules, calcite precipitated simultaneously with Fe-oxyhydroxides, whereas this was not the case for Fe (and Mn) oxyhydroxides observed within the calcareous nodules. Calcite particles in the ferromanganese nodules were covered by calcified microorganisms, suggesting a biogenic contribution to their formation. Such contributions could also play a role in the formation of the ferromanganese nodules in the lowest topographic position, presumably due to the continuous Fe supply.The formation of both ferromanganese and calcareous nodules is strongly correlated with groundwater flow in hydromorphic soils, although their primary formation periods differ. Their key properties provide valuable insights into groundwater flow characteristics and reflect microbial contributions to their formation.